Fabrication of a bismuth nanoparticle/Nafion modified screen-printed graphene electrode for: In situ environmental monitoring - Palisoc, Shirley T. (Animo Repository, 2019)
Bismuth nanoparticle (BiNP)/Nafion modified screen-printed electrodes were fabricated through screen printing and drop coating. Detection of lead (Pb2+) and cadmium (Cd2+) was performed via anodic stripping voltammetry (ASV). Optimum values of the deposition time (60 seconds) and scan rate (50 mV s-1) were obtained and utilized in the selection of the best BiNP modifier concentration of 1.0 mg. The fabricated electrodes were optimized by cyclic voltammetry, scanning electron microscopy, and energy dispersive X-ray spectroscopy. The limit of detection was found to be 280 parts per trillion and 40.34 parts per billion (ppb) for lead and cadmium, respectively. Real samples of filtered tap water, unfiltered tap water, treated wastewater, and water obtained from Manila Bay were analyzed through ASV and atomic absorption spectroscopy (AAS). The Manila Bay water samples contained lead and cadmium levels far beyond safe limits set forth by the U.S. EPA and World Health Organization while trace amounts of lead (1-2 ppb) were detected in the other water samples. The treated wastewater contained the least amount of lead while the unfiltered tap water contained the highest concentration of lead. Nonetheless, these trace amounts are well within tolerance levels set forth by government agencies. The presence of heavy metals in all water samples was validated by AAS analysis. © 2019 The Royal Society of Chemistry.